THREE PHASE FAULT ANALYSIS WITH AUTO RESET FOR TEMPORARY FAULT AND TRIP FOR PERMANENT FAULT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In any electrical power system , due to some problems such as over voltage , over current, insulator failure i.e. line to line , line to ground , double line to ground faults occur. This fault collapses the transmission system. These faults may be temporary fault or permanent fault. This fault causes some defects on equipments. To get clearance of fault & disconnect the line the circuit breaker is used. For reclosing, mechanism resets the supply line after small interruption in the event of temporary fault or it remains in tripped condition in case of permanent fault.